Online algorithms for maximizing weighted throughput of unit jobs with temperature constraints - Birks, Martin; Cole, Daniel; Fung, Stanley P. Y.; Xue, Huichao (Journal of combinatorial optimization, 2013)
We consider a temperature-aware online deadline scheduling model. The objective is to schedule a number of unit jobs, with release dates, deadlines, weights and heat contributions, to maximize the weighted throughput subject to a temperature threshold. We first give an optimally competitive randomized algorithm. Then we give a constant competitive randomized algorithm that allows a tradeoff between the maximum heat contribution of jobs and the competitiveness. Finally we consider the multiple processor case and give several tight upper and lower bounds.